2007
DOI: 10.1055/s-2007-966015
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Method for the Modification of 8-Bromoguanine via Its N9-Tetrahydrofuranyl Derivative

Abstract: M o d i f i c a t i o n o f 8 -B r o m o g u a n i n e v i a I t s N 9 -T e t r a h y d r o f u r a n y l D e r i v a t i v e Abstract: A simple and straightforward method for the introduction of some N-and O-protecting groups into 8-bromoguanine has been developed using 2-acetylamino-8-bromo-6-oxo-9-(tetrahydrofuran-2-yl)-purine as a key intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Using Mitsunobu conditions, alcohols can be used as substrates for the N-9 alkylation of guanine. This method can be used for noncanonical purines as well (for example, in the modification of 8-bromoguanine as reported by Madre et al, 30 further confirming the utility of 2-N-acetyl-6-O-DPC protection). Below, we report the synthetic routes to guanines modified with a C 10 lipophilic anchor, linked via an N-9 butyl spacer and either an ether, amide, or triazole moiety.…”
Section: ■ Introductionsupporting
confidence: 64%
“…Using Mitsunobu conditions, alcohols can be used as substrates for the N-9 alkylation of guanine. This method can be used for noncanonical purines as well (for example, in the modification of 8-bromoguanine as reported by Madre et al, 30 further confirming the utility of 2-N-acetyl-6-O-DPC protection). Below, we report the synthetic routes to guanines modified with a C 10 lipophilic anchor, linked via an N-9 butyl spacer and either an ether, amide, or triazole moiety.…”
Section: ■ Introductionsupporting
confidence: 64%
“…A reasonable choice seemed to be the tosyloxy moiety, due to its convenient introduction and subsequent removal. Therefore, a model compound, 9-[(2-acetoxyethoxy)methyl]-2-(acetylamino)-8-bromo-6-(tosyloxy)-9H-purine (11) was synthesized 3 and reacted with bromide 2e under the same conditions as in the case of purines 1, 9a-c. 9-[(2-Acetoxyethoxy)methyl]-2-[acetyl(2-bromobenzyl)amino]-8-bromo-1,9-dihydro-6H-purin-6-one (12) was isolated as the product in 37% yield (Scheme 3). It indicated that apart from benzylation at the exocyclic nitrogen, a partial or complete loss of tosyl function at the exocyclic oxygen occurred during either the benzylation reaction or the product isolation process.…”
Section: Methodsmentioning
confidence: 99%
“…As our previous attempts to synthesize the target compound from 2-(acetylamino)-8-bromo-1,9-dihydro-6H-purin-6-one and benzyl bromide resulted in the formation of N-benzylated regioisomers, 2 we decided to improve the process by using as a substrate 2-(acetylamino)-8-bromo-6-(diphenylcarbamoyloxy)-1H-purine (1) synthesized by us earlier. 3 The choice was motivated by the well-established fact that constraining 2-amino-6oxopurine from its dominant 6-lactam structure to its lactim (enolate) form by a suitable protecting group at O 6 has a beneficial effect on the regioselectivity of alkylation. 4 In this paper we present the results of the arylalkylation of purine derivative 1 and various substituted analogues.…”
mentioning
confidence: 99%
“…N -Monoacyl activated twisted amides with τ values of 40–90° are presented in Figures and . ,, Three points of amide bond geometry should be considered when discussing structures of acyclic twisted amides: (1) N -acyl activating substituent, (2) the other N-substituent, and (3) substitution at the α-carbon. It is important to note that when both of the N–C­(O) groups are acyclic, geometric distortion of the more twisted bond represents a balance between the optimum geometry for the two acyl bonds, which often leads to the flattening of the other N -acyl bond …”
Section: Acyclic Amides: Twist 40–90°mentioning
confidence: 99%
“…Examination of the examples in Figures and ,, shows that N -acyl substituents that result in a substantial twist of the amide bond include acyclic C­(O)­R, such as aromatic (aryl, 3.1 , 3.21 ; anthracenyl, 3.6 , 3.13 ), vinyl ( 3.9 , 3.39 , 3.59 ), heterocyclic ( 3.5 , 3.15 ), 1° aliphatic ( 3.14 , 3.17 , 3.23 , 3.44 , 3.55 , 3.60 – 3.61 , 3.64 ), 2° aliphatic ( 3.34 , 3.41 – 3.42 , 3.45 ), and CF 3 ( 3.51 – 3.52 ). Furthermore, the activating acyclic acyl group can be C­(S)­R (such as 3.7 , 3.11 , 3.16 , 3.24 , 3.38 ), CO 2 R (such as 3.10 , 3.35 , 3.48 , 3.50 , 3.54 , 3.57 – 3.58 , 3.62 ), C­(S)­OR (such as 3.25 ), or CONR 2 (such as 3.29 ).…”
Section: Acyclic Amides: Twist 40–90°mentioning
confidence: 99%